2006
DOI: 10.1111/j.1748-1090.2006.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

The feeding of rhinoceros in captivity

Abstract: Rhinoceros are large herbivores that are adapted for gaining energy from the fermentation of fibrous plant material. In this paper we address issues of oversupplementation of energy (leading to obesity) and minerals (particularly iron in Black rhinoceros Diceros bicornis), outline a diet design that relies on forage as the staple component with a reduction in use of pelleted compound feeds and give suggestions for supplement provision. Acquisition of adequate roughage is probably the most important step in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Based on data collected from various feeding trials, these assumptions seem to be confirmed Clauss et al 2006a). Potentially related to that, experience indicates that the black rhino can be considered a more challenging herbivore to feed in captivity compared to its grazing relative (Dierenfeld 1995;Dierenfeld 1999;Clauss et al 2006b). …”
Section: Grazing and Browsing Rhinosmentioning
confidence: 83%
See 1 more Smart Citation
“…Based on data collected from various feeding trials, these assumptions seem to be confirmed Clauss et al 2006a). Potentially related to that, experience indicates that the black rhino can be considered a more challenging herbivore to feed in captivity compared to its grazing relative (Dierenfeld 1995;Dierenfeld 1999;Clauss et al 2006b). …”
Section: Grazing and Browsing Rhinosmentioning
confidence: 83%
“…Clauss et al (2006b) interpreted the shorter MRT fluid in grazing ruminants as a consequence of a higher fluid throughput, necessary to achieve the physical mechanisms for the flotation and sedimentation described to be important for the functioning of the fermentation chamber of grazing ruminants. In terms of energy metabolism, it could be due to a higher relevance of the soluble digesta fraction in browse; in fact, the soluble fiber fraction (e.g.…”
Section: Selectivity Factormentioning
confidence: 99%
“…6e). However, this rule is not universal; for example, black rhinoceroses Diceros bicornis , although strict browsers in the wild, readily accept grass hay in captivity (Clauss & Hatt 2006). The provision of natural forages is even more problematic in captive primates (Clauss & Dierenfeld 2008), and it is not surprising that intake studies with primates on whole natural forages are absent from this data collation.…”
Section: Discussionmentioning
confidence: 99%
“…A typical example is that when feeding lower amounts of food to obese animals to facilitate weight reduction, the protein content of the diet needs to be increased in order to prevent protein deficiency and loss of lean body mass. As concerns about obesity have arisen in many zoo species [Schwitzer and Kaumanns, 2001;Clauss and Hatt, 2006;Hatt and Clauss, 2006;Cocks, 2007;Videan et al, 2007], an approach to estimate energy provision via food-similar to the estimations used in domestic carnivores [NRC Council, 2006]-would be useful in facilitating control calculations of energy intake.…”
Section: Introductionmentioning
confidence: 99%